The Influence of Peer Social Support to Student with Special Needs in Elementary Schools Inclusion - Pitaloka, Mega Ayu; Faizah, Faizah (Universitas Muhammadiyah Metro, 2017)
This study aimed to determine the effect of value social support learning through audio visual media to peer social support in Student with Special Needs in Elementary School Inclusion. The research design used quasi experiment with one group pretest-posttest design. Participants in this study were students in one of elementary school inclusion Malang grade 3, 4 and 5. The research instrument used the scale of social support peers referring to Sarafino and Smith (2011) and value social support learning through audio visual media that is social support video. Data analysis using IBM SPSS statistics 23.0 software with t-test using paired sample t-test. Finding showed that Value learning through social support video effects to peer social support in student with Special Needs in Elementary School Inclusion, with significance of 0.001 (p <0.05).